A meta-analysis of external fixation versus open reduction and internal fixation for complex tibial plateau fractures. (March 2017) - Zhao, Xing-wen; Ma, Jian-xiong; Ma, Xin-long; Jiang, Xuan; Wang, Yin; Li, Fei; Lu, Bin
Abstract: Purpose: Both external fixation (ExFx) and open reduction and internal fixation(ORIF) were used to treat complex tibial plateau fractures, but it was not sure which one was better. So we did this meta-analysis to evaluate the outcomes of ExFx and ORIF in managing complex tibial plateau fractures. Methods: Articles published before August 5, 2016 were selected from PubMed, Cochrane library, and some other electronic database. Relevant journals were also searched manually with no language limited. Two independent reviewers searched and assessed the literature. A fixed effect model was initially used for meta-analyses with RevMan 5.3. Results: When compared with ORIF, cases undergoing ExFx were more likely to return to the preinjury state at the early stage, but no difference in the later period of follow-up. However, ExFx group had higher infection rate (OR 1.98, 95% CI 1.08–3.63, P = 0.03), higher venous thromboembolism rate (OR 1.56, 95% CI 0.49–4.96, P = 0.45), higher re-operation rate (OR 0.87, 95% CI 0.47–1.62, P = 0.66) and lower compartment syndrome rate (OR 0.61, 95% CI 0.12–3.22, P = 0.56), lower TKA rate (OR 0.51, 95% CI 0.20–1.34, P = 0.17). There were no statistically significant differences in the rate of deep infection, venous thromboembolism, compartment syndrome and VTE between the two groups. Conclusion: Although external fixation may offer some advantages, both were acceptable strategies in managing complex tibial plateau fractures. According to our analysis results, we strongly recommend that selection of definitive fixators should base on the fracture patterns, soft-tissue condition as well as the injury stages in clinical practice. More important, further multicentered, randomized controlled studies should be implemented to get a more reliable and clear result. Highlights: We aimed to evaluate the effectiveness of external fixation and open reduction and internal fixation in treating complex tibial plateau fractures. ExFx had some advantages when compared with ORIF, but there were no statistically significant differences. We strongly recommend that selection of definitive fixators and time of intervention should base on the fracture patterns, soft-tissue condition and the injury stages in clinical practice. Also, we recommended further researches were needed to achieve high quality and credible results.